PENERAPAN TEKNIK ONTOLOGY UNTUK PENCARIAN DATA AKADEMIK - Jemmy Edwin Bororing; Fatsyahrina Fitriastuti (Informasi Interaktif, 2017)
ABSTRACT Semantic  Web  is a network  that  is able to understand  not only the meaning  of a word  and a concept,  but  also  a  logical  relationship  between  the  two,  so  that  a  website  can  generate  the appropriate information and desired by visitors to the website. The language used in support of the vision  of  the  semantic  web  is  the  Resource  Description  Framework  (RDF)  /  Web  Ontology Language (OWL). RDF / OWL capabilities and its facilities capable of being used to represent the meaning of terms in the web to be processed in the machine. Therefore, the research discusses the development of a model for a knowledge management system with the research domain, namely the Academic Information Systems, Faculty of Engineering, University Janabadra. Model form of web- based  prototype.  This  web  prototypes  using  semantic  web  technologies   with  application  of ontology.   Ontology   built   implemented   using   Protege   3.4.8.   besides   it  is  also   used   Java Development Kit (JDK) and the Command Prompt as an emulator prototype web. As for seeing the display prototypes use semantic web-bank. Keywords : Knowledge management system, semantic web, ontology, protégé, semantic-bank